The Value of Perioperative Chemotherapy for Patients With Hepatoid Adenocarcinoma of the Stomach Undergoing Radical Gastrectomy - Zhou, Kai; Wang, Anqiang; Wei, Jingtao; Ji, Ke; Li, Zhongwu; Ji, Xin; Fu, Tao; Jia, Ziyu; Wu, Xiaojiang; Zhang, Ji; Bu, Zhaode (Frontiers in Oncology, 2022)
Background Hepatoid adenocarcinoma of the stomach (HAS) is a rare type of gastric cancer, but the role of perioperative chemotherapy is still poorly understood. The aim of this retrospective study was to investigate the associations between perioperative chemotherapy and prognosis of HAS. Method We retrospectively analyzed patients with locally advanced HAS who received radical surgery in Peking University Cancer Hospital between November 2009 and October 2020. Patients were divided into neoadjuvant chemotherapy-first (NAC-first) group and surgery-first group. The relationships between perioperative chemotherapy and prognosis of HAS were analyzed using univariate, multivariate survival analyses and propensity score matching analysis (PSM). Results A total of 100 patients were included for analysis, including 29 in the NAC-first group and 71 in the surgery-first group. The Her-2 amplification in HAS patients was 22.89% (19/83). For NAC-first group, 4 patients were diagnosed as tumor recession grade 1 (TRG1), 4 patients as TRG 2, and 19 patients as TRG 3. No significant difference in prognosis between the surgery-first group and the NAC-first group (P=0.108) was found using PSM analysis. In the surgery-first group, we found that the survival rate was better in group of ≥6 cycles of adjuvant chemotherapy than that of <6 cycles(P=0.013). Conclusion NAC based on platinum and fluorouracil may not improve the Overall survival (OS) and Disease-free survival time (DFS) of patients with locally advanced HAS. Patients who received ≥6 cycles of adjuvant chemotherapy had better survival. Therefore, the combination treatment of radical gastrectomy and sufficient adjuvant chemotherapy is recommended for patients with locally advanced HAS.